POTONGAN KARKAS KOMERSIAL ITIK BALI BETINA YANG DIBERI RANSUM DENGAN SUPLEMENTASI DAUN PEPAYA TERFERMENTASI - N. K. M., Kristiani; Siti, N. W.; Suci Sukmawati, N. M. (Jurnal Peternakan Tropika, 2017)
This research aimed to assess the weight of female balinese duck twelve weeks commercial carcass pieces that given diets supplemented with fermented papaya leaves has been carried out in Kediri-Tabanan for three months. The experimental design used was a completely randomized design (CRD) that consists of three treatments and five replications, so there were fifteen experimental units. Every unit of the experimental using there balinese duck, one week of old and 76,37 ± 7,48  grams of body weight. The treatments were: R0 (Control diets without fermented papaya leaves), R1 (The diets containing 5% fermented papaya leaves) and R2 (The diets containing 10% fermented papaya leaves). Variables observed in this research were the weight of commercial carcass pieces on and back. The results showed that the fermented papaya leaves supplementation in ration on level 5% generate the highest weight of commercial carcass pieces, but statistically not significant (P>0.05), except on the back.  The weight of backs increased (P< 0.05) 26.0% on R1 treatment and 2.22% in R2 treatment.  The concluded that the fermented papaya leaves in rations increase  weight of back pieces, but no effect on the weight of another commercial carcass were brest, wings, thighs, drumsticks
Keywords: commercial Pieces carcass, fermented papaya leaves, ducks female bali